Top Down Innovation - Cronin, Mary J.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This Brief focuses on strategies for innovation. Top-Down Innovation discusses the barriers to successful organizational and product innovation, distills the leading theories about how to foster innovation, and presents six case studies of well-known brands that have succeeded (and in one case failed) in meeting innovation challenges. Synthesizing the lessons learned from companies that have mastered innovation over time, it provides a new perspective on the role of market-leading companies and top management in driving innovation. Since the publication of Clayton Christensen$1 (Bs pioneering Innovator$1 (Bs Dilemma in 1997, the rules of innovation have themselves been transformed. Today, innovation frequently starts at the CEO level with a vision that percolates throughout the organization. In contrast to traditional theories of technology disruption, new market entrants, and business model innovation, this study concludes that vision and leadership at the top is a decisive factor in successful innovation initiatives.s
The Challenge of Innovation -- Ford Finds Its Connection -- Netflix Switches Channels -- Nokia Drops the Torch -- Amazon Fast Tracks Information -- Stanford Spins out a Higher Education Tsunami -- Conclusion.
Keywords: Economics; Economics/Management Science; Business/Management Science, general; Innovation/Technology Management